2016
DOI: 10.18632/oncotarget.9915
|View full text |Cite
|
Sign up to set email alerts
|

Combination of radiotherapy and vaccination overcomes checkpoint blockade resistance

Abstract: The majority of cancer patients respond poorly to either vaccine or checkpoint blockade, and even to the combination of both. They are often resistant to high doses of radiation therapy as well. We examined prognostic markers of immune cell infiltration in pancreatic cancer. Patients with low CD8+ T cell infiltration and high PD-L1 expression (CD8+ TloPD-L1hi) experienced poor outcomes. We developed a mouse tumor fragment model with a trackable model antigen (SIYRYYGL or SIY) to mimic CD8+ TloPD-L1hi cancers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 43 publications
4
46
0
Order By: Relevance
“…The combination of radiotherapy with anticancer vaccines and checkpoint inhibitors has been shown to overcome immunosuppression and to increase response rates in preclinical models 72 . For example, a promising strategy involving sequential combination of radiotherapy, vaccination and anti-PDL1 in a mouse model of pancreatic cancer converts non-T-cell-inflamed cancers into T cell-inflamed cancers and mediates regression of established pancreatic tumours 72 .…”
Section: Overcoming Immunosuppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of radiotherapy with anticancer vaccines and checkpoint inhibitors has been shown to overcome immunosuppression and to increase response rates in preclinical models 72 . For example, a promising strategy involving sequential combination of radiotherapy, vaccination and anti-PDL1 in a mouse model of pancreatic cancer converts non-T-cell-inflamed cancers into T cell-inflamed cancers and mediates regression of established pancreatic tumours 72 .…”
Section: Overcoming Immunosuppressionmentioning
confidence: 99%
“…For example, a promising strategy involving sequential combination of radiotherapy, vaccination and anti-PDL1 in a mouse model of pancreatic cancer converts non-T-cell-inflamed cancers into T cell-inflamed cancers and mediates regression of established pancreatic tumours 72 . Other groups are also investigating the use of irradiated tumour cell vaccines as a strategy to boost therapeutic outcomes 7375 .…”
Section: Overcoming Immunosuppressionmentioning
confidence: 99%
“…1.0 9 10 6 OE19 or OE33 cells expressing miR-93 inhibitor, BTG3 or both as well as the negative control, suspended in 200 ll total volume, were injected subcutaneously into both dorsolateral flanks of mice (n = 12/group). On both days 28 and 35 post-inoculation, a 210 kV X-ray source was utilized for target irradiation treatment, as adapted from previous procedures with modifications [9]. Briefly, IR treatment was performed with an 8 Gy dose at 2 Gy/min on the tumor position in dorsolateral flanks with other body areas of mice protected with a lead cover.…”
Section: Human Esc Xenograft Mouse Model and Target Ir Treatmentmentioning
confidence: 99%
“…A study examining pancreatic cancer specimens from patients demonstrated the shortest OS in the group with low CD8+ T cell infiltration and high PD-L1 expression. When murine pancreatic cancer cell lines were subcutaneously injected into mice, a pancreatic mouse model was created to mimic low CD8+ T cell infiltration and high PD-L1 expression [16]. Vaccination of such mouse model using live MC 57-SIY peptide synthesized by f-moc chemistry increased CD8+ T cell infiltration, and the addition of PD-L1 blockade to vaccination enhanced the effector function of tumorinfiltrating T cells [16].…”
Section: Strategies To Enhance Activity Of Pd-1 Pathway Inhibition Inmentioning
confidence: 99%
“…When murine pancreatic cancer cell lines were subcutaneously injected into mice, a pancreatic mouse model was created to mimic low CD8+ T cell infiltration and high PD-L1 expression [16]. Vaccination of such mouse model using live MC 57-SIY peptide synthesized by f-moc chemistry increased CD8+ T cell infiltration, and the addition of PD-L1 blockade to vaccination enhanced the effector function of tumorinfiltrating T cells [16]. Providing CD8+ T cell infiltration into tumor with low mutational load was essential to elicit a synergistic immune response with immunotherapies, which was demonstrated in a phase IIA study of 2 nd line metastatic pancreatic cancer patients.…”
Section: Strategies To Enhance Activity Of Pd-1 Pathway Inhibition Inmentioning
confidence: 99%